Effect of β-blocker therapy on the level soluble ST2 protein in the blood serum in patients with heart failure with preserved and mildly reduced ejection fraction - E. V. Grakova; K. V. Kopeva; A. T. Teplyakov; M. V. Soldatenko; T. E. Suslova; V. V. Kalyuzhin (Бюллетень сибирской медицины, 2022)
Aim. To study the prognostic value of high serum concentration of soluble ST2 protein (sST2) in the development of cardiovascular events after endovascular myocardial revascularization and the possibility of using this biomarker as a target for β-blocker therapy in patients with chronic heart failure (CHF) with preserved (HFpEF) and mildly reduced (HFmrEF) left ventricular ejection fraction.Materials and methods. The study included 72 patients (aged 57–69 years, 81.94% were men) with class I–III CHF of ischemic etiology with HFpEF and HFmrEF. The patients were admitted to the cardiology department for endovascular myocardial revascularization. Before myocardial revascularization, serum concentrations of sST2 and N-terminal pro-brain natriuretic peptide (NT-proBNP) in all patients were analyzed by enzyme-linked immunosorbent assay (ELISA). Doses of β-blockers used in all patients were recalculated into a total daily dose equivalent to metoprolol succinate. Patients were divided into 2 groups depending on the median equivalent dose of metoprolol succinate (“high” ≥ 100 mg / day and “low” < 100 mg / day).Results. In patients of group 1, the serum concentration of sST2 was 30.7% higher (p < 0.001) than in patients of group 2 (40.26 [34.39; 48.92] ng /ml and 27.9 [23.05; 35.27] ng / ml, respectively), the serum NT-proBNP level in group 1 was 22.8% higher (p = 0.049) than in group 2 (167 [129; 330] ng / ml vs. 129 [125; 147] ng / ml, respectively). In patients receiving an equivalent dose of metoprolol succinate < 100 mg / day, the incidence of cardiovascular events was 34% higher (p = 0.002) than in patients receiving an equivalent dose of metoprolol succinate ≥ 100 mg/day. The ROC analysis showed that serum sST2 level ≥ 34.18 ng / ml (sensitivity 78.0%, specificity 90.0%, area under the curve (AUC) 0.906; p < 0.0001) predicts a high risk of cardiovascular events within one year. However, the serum NT-proBNP level was not an informative predictor of cardiovascular events. Conclusion. It was confirmed that increased sST2 serum concentration has high prognostic value in the development of cardiovascular events within a year after endovascular myocardial revascularization. The possibility of using this biomarker as a target for β-blocker therapy in patients with HFpHF and HFmrEF was substantiated. Aggressive use of β-blockers in the group of patients with HFpEF and HFmrEF and sST2 overexpression is preferable in order to reduce the incidence of cardiovascular events.